Understanding Of Computer Science Students' Concepts In Solving Problems Integral Based On Gender - Widyah Noviana; Windia Hadi (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study aims to determine the extent of students' understanding concepts in solving problems integral based on gender. This study employed a descriptive qualitative approach involving four computer science students from Universitas Pamulang consisting of two females and two males with varying ability levels. The results of this study that female and male students in the high category were able to restate concepts well. While on the indicator of being able to use, utilize and select certain procedures or operations, presenting concepts in various forms of representation and applying concepts or algorithms to problem solving, high-ability female students obtained a score of 3 which means they were able to answer but not correctly. Meanwhile, high-ability male students were able to master the indicator of restating the concept, while on the indicator of being able to use, utilize and select certain procedures or operations, presenting concepts in various forms of representation and applying concepts or algorithms to problem solving, high-ability male students obtained a score of 2 which means they still made mistakes. Furthermore, female and male students with low category were unable to master all the questions on the indicator namely restating concepts, being able to use, utilize, and select certain procedures or operations, presenting concepts in various forms of representation, and applying concepts or algorithms to problem solving The impact of this study is expected to be used by lecturers to design relevant learning designs to improve students' to understand the concept of integral based on gender